Progress in pediatric nephrology - Grenda, Ryszard (Przewodnik Lekarza/Guide for GPs, 2010)
Recent progress in pediatric nephrology includes introducing genetic and molecular diagnostic tools to clinical evaluation of glomerular diseases and congenital defects of urinary tract, modification of current immunosuppression protocols and evaluation of long-term risk factors in pediatric chronic kidney disease. Expected final outcome of these innovative procedures is expressed as improved therapeutic efficacy and improved life expectancy in children with severe renal diseases.